Construction of UCO solid wall / Mohamad ‘Izzuddin Mohamad Taib - Mohamad Taib, Mohamad ‘Izzuddin (2017)
Practical Training refers to work experience that is relevant to professional development prior to graduation. One of the requirements for the students of Diploma in Building Surveying to complete the program is the students must complete at least 16 weeks of Practical Training. It started on 1st December 2016 and end on 31March 2017. In term of relationship, I was lucky enough to work with a group of enthusiastic and communicative people, who for whatever reason willing to share their knowledge and experience of what they are doing. Besides, the atmosphere at SNCIPTA BINA SDN. BHD. is unique and hope that it will stays that way. The bond was created between me with my supervisor and the staffs at Contract and Construction Department. The experience gained has been an eye opening to me and I thoroughly recommend other students to do their industrial training at SN CIPTABINA SDN. BHD. enable them to have the same experience as I had at SN CIPTABINA SDN. BHD.